Influence of Phosphorus Levels on Growth and Yield of Four Lentil Varieties (Bangladesh Agronomy Journal, 2020)
An adequate supply of phosphorus (P) is important for the proper growth and yield of lentil, particularly in poor fertile soil. As such an experiment was carried out to evaluate the effects of phosphorus (P) fertilizer application on growth, yield, and yield components of lentil at the agronomy research field of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh during 2013-201. Four lentil varieties (BARI Masur-4, BARI Masur-5, BARI Masur-6, and BARI Masur-7) and four levels of P (0, 20, 40 and 60 kg P2O5 ha-1) were used in this experiment as treatment variables. Interaction of cultivar and P levels showed a significant influence on all the plant characters studied except plant height and branch production. The highest seed yield (1.98 t ha-1) was obtained from the combination of BARI Masur-7 with 40 kg P2O5 ha-1, and the lowest (1.08 t ha-1) was from BARI Masur-5 with 0 kg P2O5 ha-1. Addition of P fertilizer beyond 40 kg ha-1 decreased seed yield irrespective of varieties. Results revealed that the application of P fertilizer offers a large scope for obtaining a higher yield of lentil in Bangladesh. However, the application of P fertilizer at the rate of 40 kg P2O5 ha-1 would be the optimum for achieving higher yield irrespective of varieties.Bangladesh Agron. J. 2020, 23(1): 29-36